Peningkatan Kesadaran Bahaya dan Dampak Bullying melalui Pendidikan Stop Bullying - Prodyanatasari, Arshy; Purnadianti, Mely; Putri, Mardiana Prasetyani (Journal of Community Engagement and Empowerment, 2024)
Bullying tends to be done repeatedly to victims and can have a negative impact on victims, including discomfort, excessive depression, depression, stress, low self-esteem, trauma, and other negative impacts. The importance of knowledge on the negative impact of bullying needs to be given to students to minimize bullying, especially in the school environment. The Community Service activities (PkM) were carried out through five stages, namely: pretest, education, role playing, mentoring, and evaluation. The participants of the activity were class XII students in one public school in Kediri Regency. The selection of activity targets is based on considerations, including: (1) class XII is the highest class which will be used as a role model for the class below, (2) class XII will be assigned to be a peer tutor in transferring knowledge related to bullying actions, (3) class XII can help the school to conduct cadre in the class below, and (4) class XII can be a senior who is able to nurture, protect, and set a good example for the younger class. In the data analysis using the Wilcoxon test, it was found that the sig value was smaller than 0.05, so it can be interpreted that there is a significant difference between the pretest and posttest scores, where the posttest score is greater than the pretest score. Based on the analysis of the data obtained, it can be concluded that stop bullying education can increase students' awareness of the dangers and impacts of bullying.